2003
DOI: 10.1076/chin.9.2.142.14501
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Injury in Preschoolers: Relationship to Attention Deficit Hyperactivity Disorder

Abstract: Parental ratings of preschoolers' risk for injury, direct assessment of preschoolers' behavior thought related to risk for injury (e.g., Inattention, impulsivity) and number of documented injuries were examined in preschoolers with Attention Deficit Hyperactivity Disorder (ADHD) and their non-ADHD peers (Control). Of preschoolers with ADHD, 58.3% exhibited behavior which placed them at-risk for physical injury (0% Control), and their performance was significantly poorer on clinic-based tests. Nonetheless, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 20 publications
5
38
0
4
Order By: Relevance
“…Surprisingly, activity level did not predict medically attended injury under any level of supervision in this study. Past research examining the relation between activity level and injury has yielded inconsistent results (Byrnes et al, 2003;DiScala, Lescohier, Barthel, & Li, 1998;Schwebel, Brezausek, & Belsky, 2006), suggesting that if and when activity level predicts injury risk is not well understood. One possible explanation for the lack of consistent findings relates to age differences in child participants across studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Surprisingly, activity level did not predict medically attended injury under any level of supervision in this study. Past research examining the relation between activity level and injury has yielded inconsistent results (Byrnes et al, 2003;DiScala, Lescohier, Barthel, & Li, 1998;Schwebel, Brezausek, & Belsky, 2006), suggesting that if and when activity level predicts injury risk is not well understood. One possible explanation for the lack of consistent findings relates to age differences in child participants across studies.…”
Section: Discussionmentioning
confidence: 96%
“…Child characteristics that have been associated with injury include certain child clinical disorders (e.g., attention deficit hyperactivity disorder and oppositional defiant disorder), temperament traits (i.e., individual difference traits reflected in stable behavioral tendencies, e.g., sensation seeking), and aspects of cognitive functioning, such as attention and appraisal of risk (Bijur, Golding, Haslum, & Kurzon, 1988;Byrnes, Bawden, Beattie, & DeWolfe, 2003;Davidson, 1987;Hillier & Morrongiello, 1998;Horwitz, Morgensten, DiPietro, & Morrison, 1988;Manheimer & Mellinger, 1967;Morrongiello & Lasenby, 2006;Schwebel & Plumert, 1999). Within preschool populations, because of the difficulty in diagnosing psychopathology at very young ages and the challenge of assessing cognitions about injury risk in those with limited verbal abilities, the research has focused primarily on identifying temperament-based behavioral traits that elevate young children's risk of injury.…”
Section: Child Behavioral Attributes and Injury Riskmentioning
confidence: 99%
“…Diferenças podem ser observadas a partir de então, com dificuldades para completar tarefas, maiores níveis de atividade, menor cooperação nas atividades em grupos 36 . Os pré-escolares com TDAH estão mais propensos a acidentes leves, mas não são mais suscetíveis a lesões graves 37 . Quando o diagnóstico de TDAH é estabelecido em pré-escolares usando-se os critérios do DSM-IV, tem-se observado que as manifestações de hiperatividade e impulsividade são mais proeminentes que aquelas relacionadas ao déficit de atenção 38 .…”
Section: Transtorno Do Déficit De Atenção/hiperatividadeunclassified
“…This finding is supported by other studies in similar accident and emergency settings 7 . In contrast, a study of preschoolers with ADHD found that they were more at risk of minor injuries but not major injuries when compared to a control group of non-ADHD children 16 . Secondly, children with ADHD were more likely to have history of repeated injuries, 44.4% vs 23.4%.…”
Section: Discussionmentioning
confidence: 92%